Pengaruh Metode Field Trip Terhadap Keterampilan Menulis Karangan Argumentasi Pada Siswa Kelas IV SD Negeri 3 Simpang Rimba - Imelda Prahesti; Maulina Hendrik; Hevitria (Universitas Muhammadiyah Bangka Belitung, 2025)
This research was motivated by the low level of argumentative essay writing skills among students. The aim of this research was to determine the effect of the field trip method on argumentative essay writing skills in class IV students at SD Negeri 3 Simpang Rimba. Based on the research results, the normality test value for the pretest experimental significance was 0.003<0.05, posttest experimental significance 0.003<0.05, pretest control significance 0.001<0.05, posttest control significance 0.016<0.05, so it can be concluded that the residual value is distributed not normal, homogeneity test significance value 0.017<0.05, then it can be concluded that the two classes have non-homogeneous variance, hypothesis test significance value 0.001<0.05. So the Independent Samples T-Test test results were obtained, namely a significance value of 0.001<0.05. This shows that Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of using the field trip method on argumentative essay writing skills in class IV Indonesian language learning at SD Negeri 3 Simpang Rimba.